2021
DOI: 10.1111/ejn.15564
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal AMPA‐ and NMDA‐induced cGMP signals are mainly generated by NO‐GC2 and are under tight control by PDEs 1 and 2

Abstract: In the central nervous system, the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) signalling cascade has an established role in fine‐tuning of synaptic transmission. In the present study, we asked which isoform of NO‐sensitive guanylyl cyclase, NO‐GC1 or NO‐GC2, is responsible for generation of N‐methyl‐d‐aspartate (NMDA)‐ and AMPA (α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid)‐induced cGMP signals and which of the phosphodiesterases (PDEs) is responsible for degradation. To this end, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…86 Recently, the hippocampal cell-based assay showed that AMPA-and NMDA-GluRs are involved in the cGMP signaling under the tight control of PDE1 and PDE2. 100 Although the cyclic nucleotide signaling systems in hippocampus and corticostriatum share the common CREB pathway, they regulate some different downstream proteins/genes and are involved in distinct signaling pathways as discussed in Section 3.3. This may explain why hippocampus mainly contributes to memory and learning, but corticostriatum plays critical roles on the motivation and motor function.…”
Section: Signaling In Hippocampus Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Recently, the hippocampal cell-based assay showed that AMPA-and NMDA-GluRs are involved in the cGMP signaling under the tight control of PDE1 and PDE2. 100 Although the cyclic nucleotide signaling systems in hippocampus and corticostriatum share the common CREB pathway, they regulate some different downstream proteins/genes and are involved in distinct signaling pathways as discussed in Section 3.3. This may explain why hippocampus mainly contributes to memory and learning, but corticostriatum plays critical roles on the motivation and motor function.…”
Section: Signaling In Hippocampus Circuitmentioning
confidence: 99%
“…NO directly stimulates GC for the synthesis of cGMP to consequently activate PKG that phosphorylates CREB and several other targets for neural functions 86 . Recently, the hippocampal cell‐based assay showed that AMPA‐ and NMDA‐GluRs are involved in the cGMP signaling under the tight control of PDE1 and PDE2 100 . Although the cyclic nucleotide signaling systems in hippocampus and corticostriatum share the common CREB pathway, they regulate some different downstream proteins/genes and are involved in distinct signaling pathways as discussed in Section 3.3.…”
Section: Cyclic Nucleotide Signaling and Neuronal Functionsmentioning
confidence: 99%
“…Recent live cell fluorescence imaging of primary hippocampal neurons isolated from mice lacking NO-GC1 or NO-GC2, which were crossed with cGi-500-expressing cGMP indicator mice, revealed that NO-GC2 plays the predominant role in the generation of cGMP signals induced by N -methyl-d-aspartate (NMDA) and AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) glutamate receptors (Doris Koesling, Bochum). Furthermore, the observation that NMDA- and AMPA-induced cGMP signals are modulated by PDE inhibitors in a specific manner points to different pools of cGMP in the hippocampus, most likely in specific compartments equipped with distinct sets of PDEs (Giesen et al 2022 ).cGMP also has essential functions in mammalian embryonic development (Schmidt et al 2022 ). One important cGMP-dependent process is neuronal polarization, in which neurons form the distinct compartments of the dendrite and the axon.…”
Section: Meeting Highlightsmentioning
confidence: 99%
“…Since the stress-induced drop in central adaptive auditory responses is restorable by inhibition of 3′,5′-cyclic guanosine monophosphate (cGMP) hydrolyzing phosphodiesterase 9A (Savitska et al, 2022), we additionally asked to what extent cGMP-producing nitric oxide (NO)-sensitive (NO-GC), encoded by the mammalian Gucy1a1, Gucy1a2, and Gucy1b1 genes, and membrane-bound (GC-A) guanylyl cyclase, encoded by the mammalian Npr1 gene, may correlate with changes in auditory or hippocampal circuits acutely induced by MR and/or GR deletion. This is of particular interest because cGMP plays an important role in AMPA and NMDA receptor signaling, facilitating synaptic plasticity and memory formation (Giesen et al, 2022), specifically including functions of NO-GC (Koesling et al, 2016;Nelissen et al, 2021Nelissen et al, , 2022 and possibly also GC-A (Kroker et al, 2012). As AMPA receptor surface diffusion during LTP was shown to be changed by GR activation (Groc et al, 2008), the mRNA of activity-regulated cytoskeletal protein (Arc, also known as Arg3.1) that controls AMPA receptor trafficking during LTP/long-term depression (LTD; Guzowski et al, 1999;Plath et al, 2006;Kuipers et al, 2016) was analyzed.…”
Section: Introductionmentioning
confidence: 99%